Examining Communication Satisfaction, Confucian Work Dynamism and Job Satisfaction: A Comparative Study of International and Domestic Hotels in Hainan, China - Wang , Hua; Omar, Bahiyah (2016)
This study examines hotel employees’ communication satisfaction and job satisfaction levels in Hainan, China. The Communication Satisfaction Questionnaire (CSQ) and the Job Descriptive Index (JDI) were used in the investigation. This study also measures the Chinese working culture, Confucian work dynamism, and examines its relationship with hotel employees’ attitudes toward communication and job satisfaction. Using a survey and stratified sampling techniques, 40 sets of data were obtained from the staff working at four domestic and four international hotels operating in Hainan. Data were analysed using PLS analysis. The testing of measurement model shows that communication satisfaction measure for international hotel model was different from the measure for domestic hotel model. The results of structural model testing, on the other hand, show that both organisational communication satisfaction and Confucian work dynamism had significant effects on job satisfaction. Confucian work dynamism positively interacted with communication satisfaction in predicting job satisfaction, making it a significant moderator to the relationship between communication satisfaction and job satisfaction. All these relationships were found significant in both conditions; international and domestic hotels. The test of significant difference between the two models, however, yielded insignificant results. The findings suggest that effects of communication satisfaction and Confucian work dynamism on job satisfaction were almost equal at international and domestic hotels.